Coping with abrupt environmental change: the impact of the coastal El Niño 2017 on artisanal fisheries and mariculture in North Peru. (4th December 2018) - Kluger, Lotta Clara; Kochalski, Sophia; Aguirre-Velarde, Arturo; Vivar, Ivonne; Wolff, Matthias
Abstract: In February and March 2017, a coastal El Niño caused extraordinary heavy rains and a rise in water temperatures along the coast of northern Peru. In this work, we document the impacts of this phenomenon on the artisanal fisheries and the scallop aquaculture sector, both of which represent important socio-economic activities for the province of Sechura. Despite the perceived absence of effective disaster management and rehabilitation policies, resource users opted for a wide range of different adaptation strategies and are currently striving towards recovery. One year after the event, the artisanal fisheries fleet has returned to operating almost on a normal scale, while the aquaculture sector is still drastically impacted, with many people continuing to work in different economic sectors and even in other regions of the country. Recovery of the social-ecological system of Sechura likely depends on the occurrence of scallop seed and the financial capacity of small-scale producers to reinitiate scallop cultures. Long-term consequences of this coastal El Niño are yet to be studied, though the need to develop trans-local and trans-sectoral management strategies for coping with disturbance events of this scale is emphasized.